2007
DOI: 10.1095/biolreprod.106.059204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CDB-4022 on Leydig Cell Function in Adult Male Rats1

Abstract: CDB-4022, an indenopryridine, suppresses spermatogenesis and decreases inhibin secretion in adult male rats. In the present study, we investigated the effects of CDB-4022 on Leydig cell function. A single oral dose of CDB-4022 (2.5 mg/kg) resulted in a 2-fold decrease in serum testosterone levels after 7 days that was paralleled by a decrease in Cyp17a1 mRNA and protein levels and 17alpha hydroxylase enzymatic activity compared with vehicle-treated rats. Consistent with the lower serum testosterone levels, pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…CDB-4022 appears to target the Sertoli cell [59], as evidenced by the many parameters of Sertoli cell function that were shown to be affected within hours of CDB-4022 administration. For example, there was a significant decrease in serum inhibin B and FSH in rats treated with l -CDB-4022, suggestive of a disruption in spermatogenesis, but activin A, testosterone (however, in another study, serum testosterone was shown to decline in CDB-4022-treated adult rats [64]) and LH remained unchanged [60,61]. Equally important, the micro-tubule network, which gives the Sertoli cell its columnar shape, was disrupted and the steady-state levels of several adhesion proteins (e.g., cadherin, catenin, nectin, afadin and integrin β1) were shown to change in the rat testis following l -CDB-4022 treatment [65].…”
Section: Prospects For Nonhormonal Male Contraceptionmentioning
confidence: 99%
“…CDB-4022 appears to target the Sertoli cell [59], as evidenced by the many parameters of Sertoli cell function that were shown to be affected within hours of CDB-4022 administration. For example, there was a significant decrease in serum inhibin B and FSH in rats treated with l -CDB-4022, suggestive of a disruption in spermatogenesis, but activin A, testosterone (however, in another study, serum testosterone was shown to decline in CDB-4022-treated adult rats [64]) and LH remained unchanged [60,61]. Equally important, the micro-tubule network, which gives the Sertoli cell its columnar shape, was disrupted and the steady-state levels of several adhesion proteins (e.g., cadherin, catenin, nectin, afadin and integrin β1) were shown to change in the rat testis following l -CDB-4022 treatment [65].…”
Section: Prospects For Nonhormonal Male Contraceptionmentioning
confidence: 99%